2010
DOI: 10.1177/0194599810391628
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Neck Trauma in Operation Iraqi Freedom

Abstract: The perioperative mortality and the positive exploration rate for high-velocity penetrating neck trauma by deployed surgeons in OIF are very comparable to those rates seen in civilian centers managing low-velocity penetrating neck trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
0
31
0
5
Order By: Relevance
“…4 Overall mortality rates for penetrating neck trauma are estimated at between 3 and 6 per cent, most commonly as a result of injury to vascular structures and exsanguination. [5][6][7] The management of penetrating neck trauma is highly variable, being influenced by region and local experience. 1,2,5 The development of modern medical, anaesthetic and surgical practice, along with military experience (most recently in Iraq and Afghanistan), has resulted in improved patient outcomes and more effective management.…”
Section: Introductionmentioning
confidence: 99%
“…4 Overall mortality rates for penetrating neck trauma are estimated at between 3 and 6 per cent, most commonly as a result of injury to vascular structures and exsanguination. [5][6][7] The management of penetrating neck trauma is highly variable, being influenced by region and local experience. 1,2,5 The development of modern medical, anaesthetic and surgical practice, along with military experience (most recently in Iraq and Afghanistan), has resulted in improved patient outcomes and more effective management.…”
Section: Introductionmentioning
confidence: 99%
“…10,[12][13][14][15] Multiple studies have described the incidence and man agement of head and neck trauma during various portions of the OIF/OEF conflicts.2^1, 16,17 The Joint Facial and Invasive Neck Trauma (J-FAINT) study recently reviewed the Joint Theater Trauma Registry database and described all service members treated for head and neck trauma during 8 years of the OIF/OEF conflicts (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) 4 The J-FAINT study confirmed the high prevalence of maxillofacial injuries in current conflicts and found that midface fractures, in particu *Department of Otolaryngology-Head and Neck Surgery, Naval Medical Center San Diego, San Diego, CA 92134.…”
Section: Introductionmentioning
confidence: 99%
“…11,14 Penetrating face and neck trauma accounted for more than 75% of the injuries that necessitated critical airway control in OIF. 15 High-velocity trauma causes acute hemorrhage, tissue prolapse, and massive edema that may result in significant airway obstruction necessitating emergent airway control. 11,16 A simple and efficient way to assess airway patency is for the surgeon to ask the patient to talk.…”
Section: Airway Managementmentioning
confidence: 99%